Carboplatin and Docetaxel Chemotherapy in Nasopharyngeal Carcinoma: A Case Report - Denny Satria Utama (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2021)
Introduction: Nasopharyngeal Carcinoma (NPC) is a squamous cell malignant tumor that usually occurs in the lateral wall of the nasopharynx near the area of the eustachian tube. NPC is often found in southern Asia. In head and neck areas, NPC is one of the top five malignant which has the highest frequency tumours in Indonesia. Case report: We reported a case of a 57-year-old man with complaints of obstruction in both noses, accompanied by headache. Based on medical history, physical and Radiology examination, we concluded that he was diagnosed with Nasopharyngeal Carcinoma WHO II Stage III (T3N0M0). Histopathology revealed a differentiated non keratinizing squamous cell carcinoma in the nasopharynx. Six cycles of carboplatin and docetaxel regimen as an induction chemotherapy were planned for this patient. The patient then performed a nasoendoscopy followed by nasopharyngeal CT scan evaluation and showed a good response after Chemotherapy. Conclusion: Carboplatin and docetaxel chemotherapy management in this patient was given according to the management of nasopharyngeal carcinoma and has given a good response to the patient